Correlations between the Expression Levels of Micro-RNA146b, 221, 222 and p27Kip1 protein mRNA and the Clinicopathologic Parameters in Papillary Thyroid Cancers - Acibucu, F.; Dökmetaş, H. S.; Tutar, Y.; Elagoz, Ş.; Kilicli, F. (Experimental and Clinical Endocrinology & Diabetes, 2014)
It has been shown that miRNA 221, 222 and 146b are increasingly expressed while p27Kip1 is suppressed in papillary thyroid cancer (PTC).We investigated the association between the disease recurrence risk and the expression of miRNA 221, 222, 146b and p27Kip1 protein mRNA in these tumors. We also measured the changes in miRNAs in the presence of Hashimoto’s thyroiditis (HT).We examined formalin fixed tissue samples obtained from 77 patients. 11 out of 77 samples were identified as well differentiated tumor with uncertain malignant potential (WDT-UMP), 46 were PTC and 20 were normal thyroid tissue.Data analysis revealed that the higher risk of recurrence was associated with the higher miRNA expression levels in thyroid cancers. Higher expression levels of miRNA 146b, 221 and 222 were detected in thyroid cancer patients presenting with capsule invasion, vascular invasion or lymph node metastasis, when compared to the patients lacking these features. Furthermore miRNA expression levels were found to be significantly elevated in patients with distant metastases. A negative correlation was found between the p27Kip1 protein mRNA level and the expression levels of miRNA 221, 222 and 146b. While the expression levels of miRNA 221, 222 and 146b were found to be higher in the cases of WDT-UMP comparing to normal thyroid tissue, the p27Kip1 protein mRNA expression level was lower. No difference was found between the patients with HT and without HT regarding miRNAs expression levels.The expression levels of miRNA 221, 222 and 146b were found to be increased in cases of thyroid cancer with a high risk of recurrence. It is important to understand that these molecular changes such as miRNA expression may eventually be used to predict risk of recurrence.
Keywords: MiRNAs; thyroid cancer; Hashimoto’s thyroiditis